Initiation and emerging complexity of the collagen network during prenatal skeletal development - S Ahmed; NC Nowlan (European Cells & Materials, 2020)
The establishment of a complex collagen network is critical for the architecture and mechanical properties of cartilage and bone. However, when and how the key collagens in cartilage and bone develop has not been characterised in detail. The study provides a detailed qualitative characterisation of the spatial localisations of collagens I-III, V-VI and IX-XI in the mouse and their regional architecture variation over three developmentally significant time points: when the rudiment starts to form at E13.5 [Theiler stage (TS) 22], when mineralisation is present at E16.5 (TS25) and during the latest prenatal stage at E18.5 (TS27). Dynamic changes in collagen distribution between stages with the progression of the growth plate and mineralisation (particularly collagens I, II, V, X and XI) and dramatic changes in collagen structural organisation and complexity with maturation, especially for collagens II and XI, were observed. The future articular cartilage region was demarcated by pronounced collagens II and VI expression at TS27 and the emergence of collagens I, III, V, IX and XI in the tendon and its insertion site was observed. The present study revealed, for the first time, the emergence and maturation of key cartilage and bone collagens, in high resolution, at multiple locations across the entire rudiment, including the joint regions, at three of the most developmentally significant stages of skeletogenesis, furthering the understanding of disease and regeneration of skeletal tissues.